Optimal individual competition calendar in biathlon (the case of elite female athletes) - Olena Pidhrushna (Kharkiv State Academy of Physical Culture, 2015)
Purpose: optimization of highly skilled female biathlete preparation on the basis of creating individual competition calendars. Material and Methods: analysis of scientific-methodical literature; theoretical methods of scientific cognition; methods of mathematical statistics. Results: optimum number of starts necessary for qualitative preparation of female biathletes for the season major competition has been determined. It has been determined that in case of the season major competition to be held in February after 6 stages of the World Cup, the optimum number of starts is 13-15, and 27-30 per season (total number of available starts 34). When the season major competition is planned for March after 8 stages of the World Cup, then the average number of starts is 21 (the range from 18 to 25). Average number of starts in a season is 30 during the competitive period (the range from 24 to 34). Conclusions: the main criterion in creating individual competition calendars is the number of starts before the season major competition